Phase 2 trial design in neuro-oncology revisited: a report from the RANO group - Galanis, Evanthia; Wick, Wolfgang (The lancet. Oncology, 2012)
Summary: Advances in the management of gliomas, including the approval of agents such as temozolomide and bevacizumab, have created an evolving therapeutic landscape in glioma treatment, thus affecting our ability to reliably use historical controls to comparatively assess the activity of new therapies. Furthermore, the increasing availability of novel, targeted agents—which are competing for a small patient population, in view of the low incidence of primary brain tumours—draws attention to the need to improve the efficiency of phase 2 clinical testing in neuro-oncology to expeditiously transition the most promising of these drugs or combinations to potentially practice-changing phase 3 trials. In this report from the Response Assessment in Neurooncology (RANO) group, we review phase 2 trial designs that can address these challenges and capitalise on scientific and clinical advances in brain tumour treatment in neuro-oncology to accelerate and optimise the selection of drugs deserving further testing in phase 3 trials. Although there is still a small role for single-arm and non-comparative phase 2 designs, emphasis is placed on the potential role that comparative randomised phase 2 designs—such as screening designs, selection designs, discontinuation designs, and adaptive designs, including seamless phase 2/3 designs—can have. The rational incorporation of these designs, as determined by the specific clinical setting and the trial's endpoints or goals, has the potential to substantially advance new drug development in neuro-oncology.
Available online 30 April 2012
Gesehen am 12.06.2018